Application of Symbolic Architecture to The Design of The Fashion Carnaval Cultural Activity Center in The Jember City - Nurshella, Febriany; Widjajanti, Wiwik Widyo; Nareswarananindya, Nareswarananindya (Jurnal IPTEK, 2021)
Jember is one of cities in East Java which has been very famous in the world. This city is dubbed as a carnaval city because it organizes an annual festival namely “Jember Fashion Carnaval (JFC)”. It is a fashion carnaval that presents the creativity of Indonesian artists. This sort of event has so famed that many foreign visitors come and see. Jember Fashion Carnaval has become a great event of entertainment and tourism that make Jember and even Indonesian people proud of. Moreover, this event exhibits cultural and art fashion show in the international level. Unfortunately, a specific place which can accommodate this kind of activity has not been available yet. As a result, JFC and art show are paraded along the roads in Jember. Thus, a Cultural Activity Centre of Fashion Carnaval in Jember is necessary to be designed by employing symbolic architecture. To collect the data, the researcher implemented field study and literature study as well as descriptive analysis method. The macro concept of this design entitled iconic under the symbolic theme will make Jember as a Carnival city. Meanwhile, the micro concept of recreational land order is actualized in centered-circulation pattern getting the philosophy of JFC logo. The micro concept of adaptive shape occurs by adapting the shape of JFC symbol as the costume of building, whereas the micro concept of thematic space derives from the philosophy of JFC fashion products which have different themes for every event. The facilities provide show area, convention hall, organizer office, restaurant and inn, training and workshop, art gallery, and souvenir shop. They are designed to facilitate all activities related to JFC. Accordingly, this design is expected to be an area which can support JFC event for youths who want to develop and continue the art works produced by Indonesian people so that this event can last long and improve other subsequent events.